Mandarin Chinese L1 and L2 complex sentence reading reveals a consistent electrophysiological pattern of highly interactive syntactic and semantic processing: An ERP study - Chen, Luyao; Yang, Mingchuan; Gao, Fei; Fang, Zhengyuan; Wang, Peng; Feng, Liping (Frontiers in Psychology, 2023)
A hallmark of the human language faculty is processing complex hierarchical syntactic structures across languages. However, for Mandarin Chinese, a language typically dependent on semantic combinations and free of morphosyntactic information, the relationship between syntactic and semantic processing during Chinese complex sentence reading is unclear. From the neuropsychological perspective of bilingual studies, whether second language (L2) learners can develop a consistent pattern of target language (i.e., L2) comprehension regarding the interplay of syntactic and semantic processing, especially when their first language (L1) and L2 are typologically distinct, remains to be determined. In this study, Chinese complex sentences with center-embedded relative clauses were generated. By utilizing the high-time-resolution technique of event-related potentials (ERPs), this study aimed to investigate the processing relationships between syntactic and semantic information during Chinese complex sentence reading in both Chinese L1 speakers and highly proficient L2 learners from South Korea. Normal, semantically violated (SEM), and double-violated (containing both semantic and syntactic violations, SEM + SYN) conditions were set with regard to the nonadjacent dependencies of the Chinese complex sentence, and participants were required to judge whether the sentences they read were acceptable. The ERP results showed that sentences with “SEM + SYN” did not elicit early left anterior negativity (ELAN), a component assumed to signal initial syntactic processing, but evoked larger components in the N400 and P600 windows than those of the “SEM” condition, thus exhibiting a biphasic waveform pattern consistent for both groups and in line with previous studies using simpler Chinese syntactic structures. The only difference between the L1 and L2 groups was that L2 learners presented later latencies of the corresponding ERP components. Taken together, these results do not support the temporal and functional priorities of syntactic processing as identified in morphologically rich languages (e.g., German) and converge on the notion that even for Chinese complex sentence reading, syntactic and semantic processing are highly interactive. This is consistent across L1 speakers and high-proficiency L2 learners with typologically different language backgrounds.